Reaching Agents of Change Project: Successes, lessons and recommendations. Ex-post evaluation report - International Potato Center (International Potato Center, 2018)
The ex-post evaluation assessed the experiences, achievements and lessons from the Reaching Agents of Change (RAC) project in its three primary countries of operation, namely Mozambique, Tanzania and Nigeria. RAC was a collaborative project implemented between April 2011 and August 2015, and funded by the Bill & Melinda Gates Foundation. The goal of the project was to contribute to the efforts to reduce vitamin A deficiency (VAD) through policy reforms, advocacy for new investments, and capacity development. Vitamin A deficiency (VAD) is a critical and a widespread public health problem. CIP proved the concept that consumption and scaling up of biofortified orange-fleshed sweetpotato (OFSP) is an effective strategy for reducing VAD in children